KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN INOVASI PENDIDIKAN DI SMA YP UTAMA MEDAN - Habibah, Alfi; Nasution, Abdul Fattah; Azzahra, Aliyyah Putri; Ubaidillah, Malik (Cendekia Madani Nusantara, 2025)
Education is the main pillar in the development of a nation. The principal as an educational leader at the school level has an important role in creating a conducive and innovative learning environment. Analysis of school principal performance can provide a clear picture of the principal's ability to lead and manage educational innovation. Through this analysis, factors that support and hinder efforts to increase educational innovation can be identified. Apart from that, this analysis can also provide recommendations that can help school principals improve their performance and implement effective and sustainable educational innovations. Thus, research on analyzing the performance of school principals in improving educational innovation is very important. It is hoped that the results of this research will make a significant contribution to the development of educational policies, improving the quality of school principal leadership, as well as implementing more effective educational innovations in schools